PENGARUH MEDIA AUDIO VISUAL TERHADAP PASING BAWAH BOLA VOLI SISWA KELAS 10 SMA NEGERI 2 BENGKALIS - Yulia Purnamasari; Agus Sulastio; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine the level of influence of audio-visual media on the ability of passing down in class X SMA Negeri 2 Bengkalis in learning volleyball. The type of research used in this study was a quasi-experimental research with a quantitative descriptive approach. In this study, there was only treatment and there was a measure of success and also the absence of a control group. Based on the results of the research and discussion that the author has described, it can be concluded from the results of data analysis that it can be seen that the results of the posttest assessment of the passing ability of students in class X SMA Negeri 2 Bengkalis, for the